Developing a novel meatal areolar tissue autograft for minimally invasive tympanoplasty. Issue 10 (8th July 2020) - Chen, Yen-Chi; Huang, Chii-Yuan; Kuo, Ying-Ju; Cheng, Hsiu-Lien; Cheng, Yen-Fu; Liao, Wen Huei
Abstract : Background: We developed an easy and minimally invasive method of transmeatal tympanoplasty using meatal areolar tissue (MAT) grafts to achieve less postoperative morbidity or surgical scarring. We compared the functional and anatomical results of the developed method with conventional endaural tympanoplasty with a temporalis fascia (TF) graft. Methods: In this retrospective cohort study, 58 patients (59 ears) with simple chronic otitis media who underwent type I tympanoplasty between January 2016 and August 2018 were included. All surgeries were performed in a tertiary referral hospital and by the same senior surgeon. The tympanic membrane (TM) was repaired with either a TF or an MAT graft. Results: Healing of the perforated TM and improvement in a hearing test by air-bone gap (ABG) closure were identified. Postoperative wound conditions were also evaluated. Twenty-eight ears were grafted with MAT, and 31 ears were grafted with TF. Graft success was observed in 26 patients (92.9%) in the MAT group and 28 patients (90.3%) in the TF group. Both groups showed functional improvement compared with the preoperative measurements. The postoperative pure tone audiogram ( p = 0.737), ABG closure ( p = 0.547), and graft success rate ( p = 0.726) were not significantly different between the two groups. Neither wound dehiscence nor keloid formation was observed in our patients. Conclusion: Both MAT and TF grafts revealed satisfactory surgical and functional results. Compared with the conventional endaural approach with TF grafts, the new transmeatal approach method with an MAT graft causes relatively minimal trauma and results in better wound cosmetics. This method represents an easy, minimally invasive surgery and shows comparatively good results.